"Shunt index" can be used to predict clinically significant patent ductus arteriosus in premature neonates in early post-natal life. (2nd July 2013) - Yapakçı, Ece; Ecevit, Ayşe; Törer, Birgin; Ince, Deniz Anuk; Gökdemir, Mahmut; Gülcan, Hande; Tarcan, Aylin
Abstract Background: This study aimed to examine the differences between arterial and inferior caval vein oxygen saturation, fractional oxygen extraction, and the shunt index, which were calculated in the diagnosis of patent ductus arteriosus. Methods: Twenty-seven preterm infants were included in this study and were divided into two groups according to patent ductus arteriosus. Among them, 11 (41%) infants had haemodynamically significant patent ductus arteriosus and 16 (59%) did not have significant patent ductus arteriosus. Synchronous arterial and venous blood gases were measured during the first post-natal hours after the insertion of umbilical catheters. The differences between arterial and inferior caval vein oxygen saturation, inferior body fractional oxygen extraction, and the shunt index were calculated. Echocardiography was performed before the 72nd hour of life in a selected group of patients who had haemodynamically significant patent ductus arteriosus. Ibuprofen treatment was administered to patients with patent ductus arteriosus. Echocardiography was performed on the 72nd hour of life in preterm infants without any clinical suspicion of patent ductus arteriosus. Results: The early measured differences between arterial and inferior caval vein oxygen saturation and inferior body fractional oxygen extraction were found to be lower and the shunt index was found to be higher in the haemodynamically significant patent ductus arteriosus group than in the group without haemodynamically significant patent ductus arteriosus. Conclusion: We found that the shunt index, calculated in the first hours of life as ≥63%, predicted haemodynamically significant patent ductus arteriosus with a sensitivity of 78% and specificity of 82% in preterm newborns.